La traduction dans L’amour, la fantasia d’Assia Djebar: une tunique de Nessus. - Lievois, Katrien (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
One of the interesting features of L’amour, la fantasia by Assia Djebar is that it tries to combine historiography and autobiography by confronting both genres with the stories of Algerian women. More concretely, the author joins different textual sources in one multilingual palimpsest: the written text is based on oral texts and the French is based on Arabic, but also on English, Spanish, Turkish and German. The interrelations between the different components constitute as many translational stages, in a literal and in a figurative sense, at the heart of Djebar’s historiographical and autobiographical project. However, the explicit references the narrator makes to the communication problems between the French and the Algerians, draw our attention to the difficulty and pain involved in such an enterprise. L’amour, la fantasia is a novel based on the intertwining of sources of a different nature and from different languages, but all attempts at communication between the different cultures break down, and all the interpreters’ or translators’ efforts are doomed to fail.